1995
DOI: 10.2166/wst.1995.0439
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of odorous and nonodorous algal metabolites by permanganate, chlorine, and chlorine dioxide

Abstract: The six algal metabolites, at concentrations of 20-225 μg/l, were oxidized with potassium permanganate, chlorine, or chlorine dioxide at doses of 0.25-3 mg/l. Flavor profile analysis (FPA) was used to determine the odors of the solutions before and after oxidation. Linoleic and palmitic acids, which are odorless compounds, were oxidized to odorous products by all three oxidants. The odor intensity of β-cyclocitral (grape, sweet tobacco) and phenethyl alcohol (rose, floral) was only slightly decreased by any of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Permanganate oxidation has been already widely used in water utilities over the past decades for control of dissolved Mn(II), taste and odor compounds, and cyanotoxins, due to its comparative stability, ease of handling, and relatively low cost (Vanbenschoten et al, 1992;Dietrich et al, 1995;Rodriguez et al, 2007). In recent years, the potential application of permanganate for oxidative removal of emerging pollutants during water and wastewater treatment has received great attention (Jiang et al, 2009Jiang et al, 2012;Zhang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Permanganate oxidation has been already widely used in water utilities over the past decades for control of dissolved Mn(II), taste and odor compounds, and cyanotoxins, due to its comparative stability, ease of handling, and relatively low cost (Vanbenschoten et al, 1992;Dietrich et al, 1995;Rodriguez et al, 2007). In recent years, the potential application of permanganate for oxidative removal of emerging pollutants during water and wastewater treatment has received great attention (Jiang et al, 2009Jiang et al, 2012;Zhang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory GC and GCIMS were applied to characterize . Changes in odor types and intensities can be used as indicators of water treatment practices (Dietrich et al 1995); odors were demonstrated to appear, disappear or change when oxidants were added to water samples. A procedure for developing odor standards, based on extraction and analysis of odorous materials, was demonstrated for identifying grassy odors in fresh grass; cis-3-hexenylacetate was demonstrated to be a key odor compound (Khiari et aI., 1995).…”
Section: Biosensors and Organoleptic Methodsmentioning
confidence: 99%
“…Les composés produits par les algues à l'origine des goûts et des odeurs dans l'eau potable comprennent des aldéhydes, des alcanes, des alcènes, des alcools et des esters (DIETRICH et al, 1995 (BÜDEL et al, 2005;WEHR et SHEATH 2003).…”
Section: Les Alguesunclassified